Aerobic, muscle-strengthening, and flexibility physical activity and risks of all-cause and cause-specific mortality: a population-based prospective cohort of Korean adults - Yoonkyoung Cho; Hajin Jang; Sohyeon Kwon; Hannah Oh (BMC, 2023)
Abstract Background Studies have shown that aerobic and muscle-strengthening physical activities reduce mortality risk. However, little is known about the joint associations of the two activity types and whether other type of physical activity, such as flexibility activity, can provide similar mortality risk reduction. Objectives We examined the independent associations of aerobic, muscle-strengthening, and flexibility physical activities with all-cause and cause-specific mortality in a population-based prospective cohort of Korean men and women. We also examined the joint associations of aerobic and muscle-strengthening activities, the two physical activity types that are recommended by the current World Health Organization physical activity guidelines. Design This analysis included 34,379 Korea National Health and Nutrition Examination Survey 2007-2013 participants (aged 20-79 years) with mortality data linkage through December 31, 2019. Engagement in walking, aerobic, muscle-strengthening, and flexibility physical activities was self-reported at baseline. Cox proportional hazards model was performed to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for potential confounders. Results Flexibility physical activity (≥ 5 vs. 0 d/wk) was inversely associated with all-cause (HR [95% CI] = 0.80 [0.70-0.92]; P-trend < 0.001) and cardiovascular mortality (0.75 [0.55-1.03], P-trend = 0.02). Moderate- to vigorous-intensity aerobic physical activity (≥ 50.0 vs. 0 MET-h/wk) was also associated with lower all-cause (HR [95% CI] = 0.82 [0.70-0.95]; P-trend < 0.001) and cardiovascular mortality (0.55 [0.37-0.80]; P-trend < 0.001). Similar inverse associations were observed with total aerobic physical activity, including walking. Muscle-strengthening activity (≥ 5 vs. 0 d/wk) was inversely associated with all-cause mortality (HR [95% CI] = 0.83 [0.68-1.02]; P-trend = 0.01) but was not associated with cancer or cardiovascular mortality. Compared to participants meeting the highest guidelines for both moderate- to vigorous-intensity aerobic and muscle-strengthening physical activities, those not meeting in any guideline were associated with higher all-cause (1.34 [1.09-1.64]) and cardiovascular mortality (1.68 [1.00-2.82]). Conclusions Our data suggest that aerobic, muscle-strengthening, and flexibility activities are associated with lower risk of mortality.